2020
DOI: 10.3390/jcm9051515
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Diagnostic Tests for Detecting SARS-CoV-2 Antibodies: A Systematic Review and Meta-Analysis of Real-World Data

Abstract: SARS-CoV-2 is responsible for a highly contagious infection, known as COVID-19. SARS-CoV-2 was discovered in late December 2019 and, since then, has become a global pandemic. Timely and accurate COVID-19 laboratory testing is an essential step in the management of the COVID-19 outbreak. To date, assays based on the reverse-transcription polymerase chain reaction (RT-PCR) in respiratory samples are the gold standard for COVID-19 diagnosis. Unfortunately, RT-PCR has several practical limitations. Consequently, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
3
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(129 citation statements)
references
References 36 publications
4
118
3
4
Order By: Relevance
“…To account for the potential lack of performance of the RT-PCR for SARS-CoV-2 due to sampling quality or kinetics (sensitivity <60%) [ 11 , 12 , 13 ], a body of evidence was used for a COVID-19 diagnosis in hospitalized children between 10th March and 10th May 2020: (i) a positive SARS-CoV-2 RT-PCR test in nasopharyngeal swabs and/or (ii) typical aspects of COVID-19 in HRCT or CTPA.…”
Section: Methodsmentioning
confidence: 99%
“…To account for the potential lack of performance of the RT-PCR for SARS-CoV-2 due to sampling quality or kinetics (sensitivity <60%) [ 11 , 12 , 13 ], a body of evidence was used for a COVID-19 diagnosis in hospitalized children between 10th March and 10th May 2020: (i) a positive SARS-CoV-2 RT-PCR test in nasopharyngeal swabs and/or (ii) typical aspects of COVID-19 in HRCT or CTPA.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative approach could be mass testing of Rohingya refugees using antigen based rapid diagnostic tests [22]. Epidemiological modelling has shown that large scale testing, even with lower sensitivity, is beneficial over testing with higher accuracy but limited number of samples [23].…”
Section: Political Commitmentmentioning
confidence: 99%
“…Estas pruebas detectan, en sangre, suero o plasma (2,3), los anticuerpos generados como respuesta a la infección por SARS-CoV-2 (4,5,6). En pacientes jóvenes y sanos, la IgM y la IgA aparecen entre el cuarto y el sexto día del inicio de los síntomas, con pico en el día 14 (7,8). En pacientes inmunodeprimidos y crónicos la respues-ta se da entre el séptimo y decimocuarto día.…”
Section: Serológicasunclassified
“…En pacientes inmunodeprimidos y crónicos la respues-ta se da entre el séptimo y decimocuarto día. Por su parte, los anticuerpos IgG se retrasan en algunos casos y aparecen entre los días 15 y 21 (8,9,10,11), de modo que aparece su pico entre los días 17 y 19. Por ello, una POCT serológica realizada demasiado temprano puede no caracterizar adecuadamente el estado de los pacientes y generar falsos negativos (7,12,13,14,15).…”
Section: Serológicasunclassified
See 1 more Smart Citation